Study of Thermal Behavior in Mixed Scrap Tires (ST) And Polypropylene (PP) Plastic Using Thermogravimetry Analysis (TGA) and Differential Scanning Calorimetry (DSC) - Sofana, Ilyas; Wijayanti, Widya; Hamidi, Nurkholis (International Journal of Mechanical Engineering Technologies and Applications, 2022)
The world's rapid population growth, technological progress, and industrialization lead to an increase in fossil energy demand such as oil, coal, and natural gas. It is feared that this could lead to a scarcity of fossil energy in the future, therefore the use of alternative energy must be considered. One interesting concept to develop is waste to energy by utilizing plastic waste and also tires on vehicles. This is very possible because the two wastes contain elements of hydrocarbons which are also contained in fossil fuels so they can be processed to become alternative energy which can simultaneously reduce the population of the waste due to the increase in the world's population. This study aims to investigate the thermal behavior of scrap tires (ST) and polypropylene (PP) plastic using thermogravimetry analysis (TGA) and differential scanning calorimetry (DSC). TGA thermogram showed that the feedstock samples were degraded in the temperature range of 331,97 oC to 448,08 oC. The interpretation of the DSC thermogram that showing information about the glass transition point and the melting point of the feedstock polymer will also be presented in this study.